Application of universal design in the built environment - Abdul Rahim, Asiah; Zen, Ismawi (s.n, 2012)
This objective of this book is to disseminate information related to what is access audit, why carry out an access audit, access survey and the process of implementing it in built environment specifically to our existing buildings. It also to inform the public especially professional in the building industries such architects, engineers, planners, landscape architect, contractor, technical people from the local authorities, administrators and politician the importance of providing access in our built environment continuously in a seamless journey inside and outside buildings. This book will further disseminate information regarding access audit to built environment, explain on the procedures in accessing a building and to do the checklist on how to analyze an access audit